Control of the edge plasma modes by hot limiter biasing in the IR-T1 tokamak - Ghoranneviss, M.; Salar Elahi, A.; van Oost, G.; Arvin, R.; Mohammadi, S. (Вопросы атомной науки и техники, 2013)
Tokamak plasma modes were analyzed using the Fast Fourier Transform (FFT) in presence of hot limiter biasing system in the IR-T1 Tokamak. Fourier analysis is reliable technique for mode detection in tokamaks. For this purpose we used a poloidal array of Mirnov coils and hot limiter biasing system. After Fourier analysis of Mirnov coils data in presence of hot biased limiter, Power Spectral Density (PSD) diagram was plotted. PSD describes how the power of a signal is distributed with frequency. In this contribution we also determined edge safety factor and safety factor from Fourier based derived mode numbers q = m/n. We obtained the maximum MHD activity using power spectrum at the frequency 33 kHz. Also the edge safety factor was determined less than 3, and the values of obtained safety factor from the mode numbers are between 2 ≤ q ≤ 5. Results show that hot limiter biasing can be used for increasing the plasma safety factor.